The crude ethanol extract of Periplaneta americana L. stimulates wound healing in vitro & in vivo - Long-Jian Li; Mao-Ze Wang; Tie-Jun Yuan; Xue-Han Xu; Haseeb Anwar Dad; Chui-Liang Yu; Jian Hou; Li-Hua Peng (Chinese Medicine, 2019)
Abstract Periplaneta americana L. is a Traditional Chinese Medicine that has been used in clinic treatment of various diseases for a long history. However, the therapeutic potential and the underlying mechanism of Periplaneta americana L. in the skin wound therapy was not investigated comprehensively yet. This study aims to investigate the influence of the crude ethanol extract of PAL in the different wound stages including: (1) the migration and chemotaxis to skin cells in the first stage; (2) proliferation and cells cycle of skin cells in the second stage; (3) remodeling effect and secretion of growth factors, collagens in the third stage; (4) as well as the influence in the blood vessels regeneration in the late stage. The crude ethanol extract of PAL was shown to (1) promote the keratinocytes proliferation and regulate the cells cycle of fibroblasts significantly; (2) stimulate the migration of keratinocytes and fibroblasts obviously; (3) enhance the EGF and VEGF secretion both in vitro & in vivo; (4) accelerate the wound healing, collagen synthesis and angiogenesis. The crude ethanol extract of KFX was shown a promising therapeutic agent for the wound therapy with great efficacy to accelerate the wound healing with improved quality.